Clinical outcomes after unprotected left main coronary artery occlusion: A retrospective multicentre cohort analysis. Issue 4 (14th February 2023) - Dürig, Marco; Arroyo, Diego; Bedossa, Marc; Commeau, Philippe; Fournier, Stephane; Müller, Olivier; Barragan, Paul; Le Breton, Hervé; Puricel, Serban; Cook, Stéphane
Abstract: Aims: Unprotected left main coronary artery (ULMCA) occlusion is a rare and disastrous condition with scarce data on presentation and outcomes. Herein, we report data on patients presenting with acute coronary syndrome due to ULMCA occlusion at four different institutions. Methods: This is an international multicentre observational study. Baseline characteristics were retro‐ and prospectively collected. Clinical follow‐up was prospective. The primary outcome was in‐hospital death. Patients surviving the index hospitalization were compared with nonsurvivors to find predictors of survival. Results: The study population consisted of 55 patients. Eight patients (15%) died in the cath lab, and 23 (42%) died in hospital. Three (6%) deaths were noncardiac and due to major bleeding. Thirty‐two (58%) patients survived the index hospitalization and were discharged. These patients were followed for a median of 17.5 months during which three cardiac deaths occurred. Repeat revascularization was performed in 25% ( n  = 8). Overall mortality at maximum follow‐up was 47% ( n  = 26). The only significant predictor for hospital survival was left ventricular ejection fraction (odds ratio [OR]: 1.10 (per 1 point increase); 95% confidence interval [CI]: 1.02–1.19; p  = 0.02). Conclusion: ULMCA occlusion carries a high short‐term mortality. Patients who survive index hospitalization have similar mortality rates as compared with other st elevation myocardial infarction patients.